PENANAMAN PENDIDIKAN KARAKTER MELALUI MEDIA ATLAS DI SDN 023 SAMARINDA UTARA - Annisa Qomariah Annisa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda, 2022)
Community Service Activities aim to instill the character of students through atlas media; assist universities in formulating policies, programs and plans related to community service activities, whether carried out by students or lecturers; develop and apply knowledge; knowing the function of the media in the learning process; and the application of media in the teaching and learning process. The results of community service carried out in the classroom with seven stages and provide learning that learning media is important to use. It can be seen from the increasing enthusiasm, confidence and curiosity of students. The use of atlas media in the learning process at SDN 023 North Samarinda is essentially a process of communicating material delivery so that it is easier for students to receive the material, feel happy and gain satisfaction in learning. And can improve the learning process to be interactive, efficient, improve learning outcomes, and cultivate a positive attitude. Atlas media in learning can focus on meaningful life problems for students, stimulate interest in learning and identify geographic influences that are the focus of social studies content in elementary schools. Keywords: Character Planting, Media, Atlas